2017
DOI: 10.1371/journal.pone.0168412
|View full text |Cite
|
Sign up to set email alerts
|

Integration of MicroRNA, mRNA, and Protein Expression Data for the Identification of Cancer-Related MicroRNAs

Abstract: MicroRNAs (miRNAs) are responsible for the regulation of target genes involved in various biological processes, and may play oncogenic or tumor suppressive roles. Many studies have investigated the relationships between miRNAs and their target genes, using mRNA and miRNA expression data. However, mRNA expression levels do not necessarily represent the exact gene expression profiles, since protein translation may be regulated in several different ways. Despite this, large-scale protein expression data have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…Integrative computational bioinformatics approaches have been utilized as an effective tool to detect the potential outlier miRNAs in cancer . Furthermore, as a rational approach, preliminary detection of candidate miRNAs derived from large‐scale expression profiling data and low‐throughput experimental verification for the selected outlier miRNAs can be used to choose candidate miRNAs . In the present study, according to literature reviews and data mining for miRNAs involved in the pathogenesis of breast cancer, we selected the candidate miRNAs; to begin with, the candidate miRNAs not only should have been highly dysregulated in human BC but also they must have been easily detectable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrative computational bioinformatics approaches have been utilized as an effective tool to detect the potential outlier miRNAs in cancer . Furthermore, as a rational approach, preliminary detection of candidate miRNAs derived from large‐scale expression profiling data and low‐throughput experimental verification for the selected outlier miRNAs can be used to choose candidate miRNAs . In the present study, according to literature reviews and data mining for miRNAs involved in the pathogenesis of breast cancer, we selected the candidate miRNAs; to begin with, the candidate miRNAs not only should have been highly dysregulated in human BC but also they must have been easily detectable.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Furthermore, as a rational approach, preliminary detection of candidate miRNAs derived from large-scale expression profiling data and low-throughput experimental verification for the selected outlier miRNAs can be used to choose candidate miRNAs. 22,23 In the present study, according to literature reviews and data mining for were culled to be analyzed and confirmed by RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, let-7a/b could indirectly suppress the β -catenin pathway, which in a different way could be activated by lncRNA FTHIP3 [111], but also is regulated by molecular axis miR-21-GAS5-miR-135b [112]. This unexpected crosstalking between ncRNA signaling could shed a light on expression relationships among ncRNAs and mRNAs, which have been frequently reported in cancer literature, but to date have not been satisfactorily explained [157159]. This scenario is made more complex by the tissue-specific expression pattern of all ncRNAs, which could effectively influence the occurrence of specific interactions among ncRNAs.…”
Section: Noncoding Rna Network: Future Perspectives For New Therapmentioning
confidence: 99%
“…Therefore, levels of miRNAs and the cognate target mRNA would correlate only in certain tissues. In addition, under certain circumstances, the effect of an miRNA on its target can only be observed when the protein level is measured (Li et al, 2015 ; Seo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%